Hot or not: Which features make FinTechs attractive for investors? - Johannes Klein; Leonard Stuckenborg; Jens Leker (The Journal of Entrepreneurial Finance (JEF), 2020)
Attracting investors and generating funding is a key issue for all start-ups. The information asymmetries between investor and start-up need to be reduced. Despite the overwhelming literature on venture capital financing and different signals reflecting venture quality, pinpointing the signals which impact funding decisions remains an open issue. This study presents an empirical examination of the effectiveness of different signals to convince investors and generate funding. We examine the impact of signals concerning venture quality (classic ones such as human capital, intellectual capital and social alliance/network capital as well as the strategic orientation in terms of business model patterns. Based on a comprehensive sample of more than 101 German FinTechs, our study delivers empirical evidence that human capital as well as the strategic orientation positively impacts a FinTech's attractiveness. However, our chosen measures for intellectual capital and social network/alliance capital result in negative effects.
Keywords: M13; G24; L26; 650; Alliance capital; Intellectual capital; human capital; Strategic Orientation; FinTechs; Funding